2008
DOI: 10.5014/ajot.62.5.522
|View full text |Cite
|
Sign up to set email alerts
|

Playful Interaction: Occupational Therapy for All Children on the School Playground

Abstract: We examined the impact of an intervention on the playfulness of 5- to 7-year-old children who are developing typically. Materials that had no defined purpose were placed on a school playground for 11 weeks. The Test of Playfulness (ToP) was used to compare videotaped play segments pre- and postintervention. Teachers who did playground duty were interviewed regarding changes in play. ToP data were analyzed using a Wilcoxon signed-ranks test. Interview data were analyzed for themes. ToP scores were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 14 publications
3
61
0
Order By: Relevance
“…The inter-personal (social) themes identified within Bundy's earlier studies (Bundy et al, 2009;Bundy et al, 2008) were evident among students of all age groups during this intervention. Many of the teachers in this study reported that students were using the LEAP intervention materials to play with students they wouldn't generally associate with.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The inter-personal (social) themes identified within Bundy's earlier studies (Bundy et al, 2009;Bundy et al, 2008) were evident among students of all age groups during this intervention. Many of the teachers in this study reported that students were using the LEAP intervention materials to play with students they wouldn't generally associate with.…”
Section: Discussionmentioning
confidence: 92%
“…Strategies to further enhance the successful maintenance of the LEAP intervention could be to include a co-ordinator or key teacher to advocate for the intervention and to monitor the condition of the materials (Hoelscher et al, 2003;Rogers, 2002;Webber et al, 2008). As the LEAP intervention builds upon previous research (Engelen, et al, 2013;Bundy et al, 2009;Bundy et al, 2008) by examining additional health outcomes and a larger age range, future research could investigate the implementation of movable/recycled materials during after school periods and across multiple school environments to complement or replace conventional school playgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The likelihood of children experiencing even minor injuries on the playground was small, but the fears of a few adults could create enough uncertainty and discomfort within the participants to threaten the longevity of the new playground experiences (Bundy et al, 2008;). Thus, plans for managing the materials and integrating them into the routine of school recess were dependent on adults' agreement that some risk or uncertainty in the moment was acceptable in exchange for potential benefits to children's present and future well-being.…”
Section: Adults' Response To Risky Playmentioning
confidence: 99%
“…Other studies were not useful because of methodological limitations (e.g., Bharadwaj, Daniel, & Matzke, 2009;Shoener, Kinnealey, & Koenig, 2008). Bundy et al's (2008) study highlights the role that occupational therapists could have in modifying school yards and community playgrounds so that they promote engagement in creative play-related activities, whereas Hilton and colleagues' (2008) study illustrates that occupational therapists need to be aware that children with highfunctioning autism spectrum disorders may have difficulties related to out-of-school participation. Ashburner et al's (2008) work is also germane to clients with autism spectrum disorder, indicating that certain sensory processing patterns (e.g., sensory underresponsiveness and sensory seeking) of primary school-age children may be related to academic underachievement.…”
Section: Basic Researchmentioning
confidence: 99%